Pengaruh Pengetahuan Lingkungan, Persepsi Dan Perilaku UMKM Batik Di Pekalongan Dalam Mengimplementasikan Green Economy - Wijaya, Kusuma; Dewi, Siska; Safitri, Anni (Jurnal Iqtisaduna, 2022)
In the era of transformation 5.0 as it is today, environmental sustainability is one of the common problems for all communities around the world. Pekalongan City is one of the centers of batik fabric industry in Indonesia. Several rivers in Pekalongan City are declared to have been polluted due to pollution of textile dye waste. The existing cloth factory in Pekalongan City dumps its waste directly into the river. MSMEs (Micro, Small & Medium Enterprises) are one of the economic actors that have such a large role in the national economy. The purpose of this study is to determine the influence of environmental knowledge, perceptions and behaviors of Batik MSMEs in Pekalongan in implementing the Green Economy. This study used quantitative methods and to process data using SPSS 20 from respondent data of around 97 from batik MSME actors in Pekalongan. From the results of this study, it shows that knowledge affects the perception of MSMEs in implementing the green economy. The perception oftheattitude of MSMEs in implementing the green economy. Knowledge affects the behavior of MSMEs in implementing the green economy through the perceptionof MSME practices. Keywords: Environmental Knowledge, Perception, Behavior, Green Economy